2001
DOI: 10.1021/ma0002545
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Pressure Dependence of the Phase Boundaries in PEE−PDMS and PEP−PDMS Binary Homopolymer Blends and Diblock Copolymers

Abstract: Both polymer blends and diblock copolymers have been investigated with small-angle neutron scattering (SANS) in varying temperature and pressure fields. Four samples were studied: a polymer blend of near critical composition and the corresponding symmetric diblock copolymer of poly-(ethylethylene) (PEE) and poly(dimethylsiloxane) (PDMS) and two further symmetric diblock copolymers of poly(ethylenepropylene) (PEP) and PDMS differing in their molecular mass. From the SANS results the phase transition temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…The measure of the miscibility is the so-called Flory interaction parameter, , and the temperature and concentration dependence of MST can be quantitatively discussed with this parameter [10]. Pressure P is also an environmental parameter governing the phase behavior of block copolymers, and a number of works are reported on pressure-induced microphase separation of blockcopolymer systems [11][12][13][14]. Steinhoff et al [12] and Schwahn et al [13] observed a reentrant shift of the order-disorder transition temperature in block-copolymer melts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The measure of the miscibility is the so-called Flory interaction parameter, , and the temperature and concentration dependence of MST can be quantitatively discussed with this parameter [10]. Pressure P is also an environmental parameter governing the phase behavior of block copolymers, and a number of works are reported on pressure-induced microphase separation of blockcopolymer systems [11][12][13][14]. Steinhoff et al [12] and Schwahn et al [13] observed a reentrant shift of the order-disorder transition temperature in block-copolymer melts.…”
mentioning
confidence: 99%
“…Pressure P is also an environmental parameter governing the phase behavior of block copolymers, and a number of works are reported on pressure-induced microphase separation of blockcopolymer systems [11][12][13][14]. Steinhoff et al [12] and Schwahn et al [13] observed a reentrant shift of the order-disorder transition temperature in block-copolymer melts. However, to our knowledge, there have been no papers that deal with pressure-induced microphase separation of block-copolymer aqueous solutions by focusing on hydrophobic solvation.…”
mentioning
confidence: 99%
“…[90] Since the UCST/UDOT systems are characterized by endothermic mixing (DH mix > 0), a negative DV mix shifts the UCST/UDOT to a lower temperature, whereas a positive DV mix serves to increase the UCST/UDOT, with increasing P. [90] Both pressure-induced increases [84,[90][91][92][93] and decreases [90,94] in UCST/UDOT have been experimentally observed. Complex P-T relationships wherein the temperature initially decreases and then increases upon pressurization have likewise been reported for UCST/UDOT [95,96] and LCST/LDOT systems. [97,98] …”
Section: Solvent and Pressure Effectsmentioning
confidence: 67%
“…Most experiments under pressure have been performed to elucidate the effect of pressure on miscibility of polymer blends [10][11][12][13][14][15]. Almost no researches had been done on the details of nano-structures of PLA/PEG blends under pressure.…”
Section: Introductionmentioning
confidence: 99%